Chromophore Multiplication To Enable Exciton Delocalization and Triplet Diffusion Following Singlet Fission in Tetrameric Pentacene - Hetzer, Constantin; Basel, Bettina; Kopp, Sebastian M.; Hampel, Frank; White, Fraser J.; Clark, Timothy; Guldi, Dirk Michael; Tykwinski, Rik R. (Angewandte Chemie International Edition, 2019)
A tetrameric pentacene, PT, has been used to explore the effects of exciton delocalization on singlet fission (SF). For the first time, triplet decorrelation through intramolecular triplet diffusion was observed following SF. Transient absorption spectroscopy was used to examine different decorrelation mechanisms (triplet diffusion versus structural changes) for PT and its dimeric equivalent PD on the basis of the rate and activation barrier of the decorrelation step. Charge-separation experiments using tetracyano-p-quinodimethane (TCNQ) to quench triplet excitons formed through SF demonstrate that enhanced intersystem crossing, that is, spin catalysis, is a widely underestimated obstacle to quantitative harvesting of the SF products. The importance of spatial separation of the decorrelated triplet states is emphasized, and independent proof that the decorrelated triplet pair state consists of two (T-1) states per molecule is provided.
CRIS-Team WoS Importer:2019-10-04